Constructing PA6/PS composite foam with porous and hybrid isolation structure to synergistically control absorption and electromagnetic interference shielding effectiveness. Issue 29 (23rd May 2022) - Wu, Bozhen; Zhu, Kaiqi; Yang, Yuhao; Wen, Xinghan; Liu, Renrong; Zhu, Honghao; Yang, Jintao
Abstract: Isolation structure has been proven to be an effective method for constructing electromagnetic shielding composites, achieving high electrical conductivity with shallow filler content and high‐efficiency electromagnetic shielding. However, there are still many challenges in further optimizing the design and improving absorption. This article designed a hybrid isolation structure using nylon magnetic microspheres and polystyrene (PS). First, we prepared PA magnetic microspheres (Ni@PA6M) with Ni nanoparticles uniformly dispersed by the reaction induced phase separation (RIPS) method, then mixed with MWCNT and PS at high speed and formed by hot pressing. Under the optimized ratio, the hybrid structure has more interfaces and a more complete conductive network. Simultaneously, the magnetic microspheres can promote the absorption of electromagnetic waves, thereby improving the electromagnetic shielding performance of the material. When the MWCNT content is 7 wt%, Ni@PA6M:PS = 7:3, the total shielding effectiveness (EMI SE T ) and reflection coefficient ( R ) of the composite reached 28.6 dB and 0.77, respectively, while the EMI SE T and R of the composite constructed with pure nylon microspheres and PS are 26.1 dB and 0.74, respectively. Further, using supercritical CO2 foaming technology to foam the PS phase in the composite to form many cells can improve the impedance matching and absorption of electromagnetic waves. The results show that introducing the cell structure reduces the reflection coefficient ( R ) from 0.77 to 0.69, and the EMI SE T drops to a certain extent. Introducing the hybrid isolation and porous structure we designed provides a new idea for creating electromagnetic shielding materials for isolation structures. Abstract : This study is the first to design and fabricate PA6/PS/MWCNT electromagnetic shielding composites with hybrid isolation structure by combining in‐situ anionic polymerization of caprolactam with high‐speed mixing. It has good electromagnetic shielding effect and low reflection coefficient obtained by supercritical CO2 foaming treatment.